The development of movement system of the second six-legged robot PTE UNIMA - Mamahit, Calvin E J; Sanggola, Mildes (Universitas Negeri Padang, 2021)
Engineering technology in robotics for the present era is no longer new, especially in high education, marked by Indonesian robot contests routinely held annually by the national achievement center. The participants in this event are groups of students from all higher education institutions spread throughout Indonesia. The development of robotics technology is now faster to spur individuals and students to compete to conduct research and development in robotics. The study aims to develop a six-legged robotic motion system or so-called hexapod. The research was conducted using the Addie model research method consisting of five stages, namely, analyze stage to analyze the needs of the development of the robotic motion system and analysis of the needs of tools and materials to be used. The design stage of designing the mechanical structure of the robot both in terms of hardware and in terms of robot software, the development stage of developing a six-legged robot's motion system to be more stable and more efficient in moving, the implementation stage is a test stage of the robot's motion system that has been developed. The evaluation stage is the last stage of this development research; at this stage, the evaluation is done to ensure the robot's motion system is feasible to use.